Survival of Xanthomonas campestris pv. campestris in the phyllosphere and rhizosphere of crops - da Silva, João César [UNESP]; da Silva Júnior, Tadeu Antônio Fernandes [UNESP]; Soman, José Marcelo [UNESP]; do Nascimento, Daniele Maria [UNESP]; de Melo, Luana Laurindo [UNESP]; Oliveira, Letícia Rodrigues [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Maringoni, Antonio Carlos [UNESP] (Springer Nature, 2021)
Aims: Xanthomonas campestris pv. campestris (Xcc) survival was evaluated in the phyllosphere and rhizosphere of 20 crop species, as well as in the rhizosphere of cabbage cultivated in six soil types. Methods: The crops aerial parts were inoculated, and the rhizosphere soil was infested with bacterial suspension (107 CFU.mL−1) of 3098C Xcc strain, which is rifampicin-resistant and pathogenic to brassica plants. Xcc recovery from the samples was performed in a semi-selective culture medium. Results: The highest average survival periods of Xcc in the phyllosphere were obtained from cabbage (70 days), tomato (67 days), wheat and pumpkin (63 days), black oat and radish (56 days) and sweet pepper (49 days). Low Xcc survival occurred in the rhizosphere of most crops evaluated when compared to the soil in the absence of plants. The highest average period of survival in the rhizosphere was observed for cabbage (53 days). Survival periods in lettuce, pumpkin, wheat and mustard ranged from 21 to 28 days. In the rhizosphere of cabbage cultivated in six soils, survival periods ranged from 8 to 17 days. Conclusions: Sunflower, carrot, zucchini, spinach, sunn hemp, sorghum, maize and chive are recommended for rotating systems with brassicas because Xcc showed low survival in the phyllosphere and rhizosphere of these crops.
Keywords: Bacteria; Black rot; Crop rotation; Soil